Pengaruh tebal kaca terhadap kinerja kolektor surya pelat datar dengan menggunakan absorber batu granit - M. Wirawan; M. Mirmanto; F. Pramudia; I.G.A.K.C Adhi; R. Sutanto (Dinamika Teknik Mesin: Jurnal Keilmuan dan Terapan Teknik Mesin, 2018)
This paper presents the experimental data of the use of granite stone as an absorber of the tested solar colecctor. The purpose of this study is to know the effect of the cover thickness of the collector. Three different thickness of the glass cover of the collector, i.e. 3 mm, 5 mm, and 8 mm, were tested. Three identical collectors were utilized in this current study, and the collectors were placed facing North. The dimension of the granite absorber is 100 cm x 80 cm x 10 cm and the arrangement of the pipes in the collector is parallel with 7 pipes. The water used to remove the heat from the absorber was flowed naturaly due to the gravity. The water volumetric flow rates employed were 300 cc/min, 400 cc/min and 500 cc/min which were measured using a glass volume meter and a stop watch. The research results show that energy come to the absorber (Qin), energy absorbed by the absorber (Quse), and the temperature of water increase with the time. All of them have a peak at around 12.00-14.00 Wita. The thicknes of the glass cover affect the performance of the collectors. The glass cover thickness of 5 mm results in the better performance than that of the two others.